The Role of Therapeutic Communication in Providing Health Education for Midwifery Services - Lili Purnama Sari (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Midwifery practice does not only emphasize clinical aspects, but also includes the role of therapeutic communication which includes interpersonal communication and counseling, both individually and in groups. Objective: This study aims to determine the role of therapeutic communication in providing health education to midwifery services. Method: The study used a quantitative method with a sample of 30 people selected through the Accidental Sampling technique. Result and Discussion: The results of the study showed a p value = 0.003 which is smaller than α (0.05). This study indicates that there is a significant relationship between the application of therapeutic communication in providing health education with the quality of midwifery services. Conclusion: Therefore, it can be concluded that effective therapeutic communication plays an important role in supporting the successful delivery of health education and improving the quality of midwifery services.